Double and triple ionisation of isocyanic acid - Eland, JHD; Squibb, RJ; Sterling, AJ; Wallner, M; Roos, AH; Andersson, J; Axelsson, V; Johansson, E; Teichter, A; Stranges, S; Brunetti, B; Dyke, JM; et al. (Nature Research, 2020)
Double and triple ionisation spectra of the reactive molecule isocyanic acid (HNCO) have been measured using multi-electron and ion coincidence techniques combined with synchrotron radiation and compared with high-level theoretical calculations. Vertical double ionisation at an energy of 32.8 ± 0.3 eV forms the 3A” ground state in which the HNCO2+ ion is long lived. The vertical triple ionisation energy is determined as 65 ± 1 eV. The core-valence double ionisation spectra resemble the valence photoelectron spectrum in form, and their main features can be understood on the basis of a simple and rather widely applicable Coulomb model based on the characteristics of the molecular orbitals from which electrons are removed. Characteristics of the most important dissociation channels are examined and discussed.